Osteologia do neurocrânio de Iguana iguana iguana (Squamata: Iguanidae) - Lima, Fabiano C.; Pereira, Kleber F.; Abe, Augusto S. [UNESP]; Sebben, Antonio (Colégio Brasileiro de Patologia Animal - CBPA; Empresa Brasileira de Pesquisa Agropecuária (EMBRAPA), 2014)
Skull represents the segment with conspicuous adaptations that, in lizards, may be conservative or promoted by selective pressures. The aim of assisting the morphological knowledge of reptiles, we provide a detailed description of the neurocranium of Iguana iguana iguana based on analysis of three dried adult skeletons. The skull of this species has basal characteristics in lizards without closure of cranial openings and general triangular shape. Bony structures that form the caudal base have many fusions, especially on the floor. In the caudal face the exoccipital and the opisthotic are fused and form the otooccipital, which contributes to the formation of the lateral part of the condyle. The central part is formed by the condyle supraocciopital. Fusions and skeletal structures in Iguana are similar to other lizards. There are no autopomorphies in the neurocranium for this species.

O crânio representa o segmento com conspícuas adaptações que, nos lagartos, podem ser conservativas ou impulsionadas por pressões seletivas. Objetivando subsidiar o conhecimento morfológico dos répteis, fornecemos uma descrição detalhada dos ossos que formam o neurocrânio de Iguana iguana iguana com base na análise de três esqueletos secos de espécimes adultos. O crânio da referia espécie possui características basais entre os lagartos sem o fechamento das aberturas cranianas e formato geral triangular. As estruturas ósseas que formam a base craniana apresentam muitas fusões, principalmente no assoalho. Na face caudal o exoccipital e o opistótico estão fundidos e formam o otoccipital, que contribui para a formação dos terços laterais do côndilo occipital. A parte central do côndilo é formada pelo supraoccipital. Fusões e estruturas esqueléticas presentes em Iguana são similares aos demais lagartos. Não foram descritas autapomorfias no neurocrânio para esta espécie.
Neurocranium osteology of Iguana iguana iguana (Squamata: Iguanidae)
Keywords: Iguana iguana iguana; green iguana; reptiles; neurocranium; skull; skeleton; Iguana iguana iguana; iguana verde; répteis; crânio; esqueleto